Teaching self-care: understanding the learned and lived self-care experiences of social work students. - Lamb, Jenny; Peterson Dealey, Rhonda (Social Work Education, 2025)
Professional self-care in social work is regarded as paramount to ethical and competent practice. However, the absence of an agreed upon operationalization of self-care leaves social work educators directionless on the teaching and modeling of self-care. This study investigated the learned and lived self-care experiences of BSW and MSW students (n = 80) in their final field education experience. Data collection included an anonymous online survey, focus groups, and a follow-up online survey. Broadly, students were asked to consider three aspects of self-care: 1) their understanding of self-care, including the sources of that understanding; 2) their experienced internal and external barriers to self-care; and 3) the interface between self and systems when practicing self-care. Utilizing a general inductive approach to data analysis, several evocative themes emerged suggesting gaps between the learned experience and the lived experience of self-care including the conflict between familial or cultural values and formal self-care education, a divide between their positive experiences with self-care and their actual performance of self-care, and inhibitory components of professional systems to the personal practice of self-care. Students exhorted their social work educators to model self-care, teach it explicitly, provide in-vivo practice opportunities, and to understand the student experience.